Mindfulness for Optimizing Mental Health in Sports: A Systematic Literature Review and Implications for SDG 3 - Dhevy Puswiartika; Humaedi Humaedi; Addriana Bulu Baan; Ajriana Safana (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To synthesize and critically appraise recent empirical evidence on the role of mindfulness in optimizing mental health in sports, particularly among athletes and coaches. Method: Employed a systematic literature review using the PRISMA guidelines. Articles were searched through ScienceDirect and Google Scholar using the keywords mindfulness, sport, and mental health. The inclusion criteria covered English-language, open-access journal articles published between 2020 and 2024 that involved athletes or coaches and discussed dispositional mindfulness, mindfulness practice, or mindfulness-based interventions. After screening 65 full-text articles, 14 studies met the eligibility criteria and were analyzed narratively. Results: The findings indicate that mindfulness contributes positively to sports performance and mental health outcomes. Mindfulness-based interventions were reported to improve resilience, self-confidence, emotion regulation, subjective performance satisfaction, mindful awareness, well-being, and sleep quality. In addition, mindfulness helped reduce stress, anxiety, depression, tension, and the likelihood of choking during sports performance. Novelty: The review highlights mindfulness not only as a psychological training strategy to enhance sports performance but also as a promising approach to optimizing mental health in sports. The study also identifies the need for more rigorous randomized controlled trials with larger sample sizes and across diverse sports contexts. Furthermore, the findings offer important implications for SDG 3 (Good Health and Well-Being) by supporting the integration of evidence-based mindfulness approaches to promote psychological well-being, resilience, and mental health among athletes and coaches